X fluorescence spectrometry for rapidly and synchronously determining primary and secondary components of silicon, calcium, aluminum and phosphorus in silicon nitride alloy

Through the combination of the cast glass sheet method and X-fluorescence spectroscopy, the problem of slow multi-component detection speed and low precision of silicon nitride alloy is solved, and fast and accurate multi-component synchronous determination is achieved, reducing detection cost and time.

CN120559002APending Publication Date: 2025-08-29SHANDONG IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510722139.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

It is difficult to quickly and accurately determine the primary and secondary amounts of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys in the prior art. The traditional method has slow detection speed, low precision, and has large interference in complex substrates, and lacks fast and accurate detection methods.

Method used

The melted-cast glass sheet method combined with X-fluorescence spectrometry was used to prepare glass sheet samples that satisfies the determination of X-fluorescence instruments by pre-treating the samples and using lined crucibles, oxidizing agents and fluxes, thereby eliminating matrix interference and achieving multi-component synchronous determination.

Benefits of technology

It realizes rapid and accurate detection of multi-components in silicon nitride alloys, reduces detection cost and time, improves detection efficiency, and fills the gap in fast and accurate measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical analysis, and particularly relates to an X-ray fluorescence spectrometry method for rapidly and synchronously determining primary and secondary components of silicon, calcium, aluminum and phosphorus in a silicon nitride alloy. According to the method, a crucible is lined with lithium tetraborate, an oxidizing agent and a fusing agent in a certain proportion are added, and a proper sample pre-melting oxidation procedure is set, so that the rare earth nitrogen alloy can be made into a glass casting sheet sample meeting the measurement requirement of an X-ray fluorescence instrument, and the content of various components in the alloy can be synchronously tested through the X-ray fluorescence spectrometry; the detection time is greatly saved, the electricity and gas expenses are saved, the detection cost is reduced, and meanwhile, the blank of no method for rapidly and accurately determining the elements in the rare earth nitrogen alloy at the same time is filled up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical analysis, and particularly relates to an X-ray fluorescence spectrometry method for rapidly and synchronously determining the major and minor multi-component amounts of silicon, calcium, aluminum and phosphorus in a silicon nitride alloy. Background Art

[0002] Silicon nitride alloys have a significant effect on improving refractory materials and steel performance. Silicon nitride alloys are mixtures containing multiple elements such as silicon, calcium, and aluminum. Among them, Si3N4 is a residue that is difficult to dissolve with strong acids. Si3N4 is an atomic crystal formed by silicon atoms and nitrogen atoms. It belongs to the hexagonal crystal system and has a hexahedral structure. Its Si-N bond is strong, its chemical properties are stable, and it is extremely resistant to oxidation and corrosion. Conventional hydrofluoric acid, perchloric acid, or nitric acid are also difficult to dissolve under heating conditions. Borates can melt Si3N4 under high temperature conditions, which can avoid the use of large amounts of highly corrosive hazardous chemicals in the process of detecting element content. When melting borates to treat samples, a platinum crucible is required. Under high temperature conditions, reducing substances such as silicon and iron in the nitrogen alloy easily undergo alloying reactions with the platinum crucible, severely corroding the crucible.

[0003] Nitrogen alloys are a new type of alloy used by steelmakers. Accurate testing of their chemical composition is essential during both production and use. Traditional chemical analysis methods (such as gravimetric methods) lag significantly behind emerging instrumental analysis methods in terms of speed and precision. Major and minor components require separate testing due to their wide content ranges, resulting in complex and time-consuming testing and high labor intensity for testers. While industry professionals are actively researching new testing technologies to replace traditional chemical analysis methods, there is currently no mature, rapid, or accurate method for testing silicon nitride alloys.

[0004] X-ray fluorescence spectrometry (XRF), a relatively mature component analysis method, is widely used in fields such as metallurgy, geology, environment, chemical engineering, and materials science. XRF analysis primarily targets bulk solids, powders, and liquids. Powdered solids, such as cement, coal, and dust, are the most commonly analyzed. XRF analysis using powder pellets is simple, rapid, and economical, making it widely used when the analytical workload is high and precision requirements are not high. It is also commonly used for trace element analysis. However, XRF analysis using pellets is significantly affected by the matrix, and while qualitative analysis may be sufficient, precise quantitative analysis is less than ideal. Summary of the Invention

[0005] In response to the shortcomings of current analytical methods, and in order to achieve rapid and accurate detection and analysis of multiple components in silicon nitride, the present invention provides a fused-glass sheet method for rapidly determining the major and minor amounts of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys. By introducing the fused-glass sheet method, the influence of particle size effect and mineral effect is effectively eliminated, the interference of complex matrices is fully reduced, and the analytical accuracy of each component is improved.

[0006] The present invention provides a method for rapid and simultaneous determination of the major and minor components of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys using X-ray fluorescence spectrometry. This method allows for direct determination of elements such as silicon with relatively high content without diluting the test solution. Furthermore, a novel method for preparing pre-treated fused glass sheets has been developed. This method utilizes a lined crucible, adds a certain proportion of oxidant and flux, and establishes a suitable sample pre-melting and oxidation procedure. This allows the production of fused glass sheet samples from silicon nitride alloys that meet the requirements of X-ray fluorescence instrumentation, thereby enabling simultaneous testing of the major and minor component contents using X-ray fluorescence spectrometry.

[0007] A method for rapidly and simultaneously determining the major and minor amounts of silicon, calcium, aluminum, and phosphorus in a silicon nitride alloy by X-ray fluorescence spectrometry comprises the following steps: S1. Preprocessing: S101. Weigh ingredients: Weigh the sample, lithium carbonate, and potassium nitrate, stir them evenly, and transfer them into a prefabricated crucible of anhydrous lithium tetraborate; Weigh anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold crucible, then place the prefabricated anhydrous lithium tetraborate crucible inside the platinum-gold crucible; S102, pre-oxidation: The platinum-gold crucible was placed in a muffle furnace heated to 500±50°C, kept warm, then heated to 750±50°C, kept warm, taken out, and cooled.

[0008] S2, melting: Lithium bromide is added dropwise to the platinum-gold crucible, and the crucible is placed in an automatic melting machine that has been preheated to the melting temperature to automatically melt the sample to form a glass melt, which is then dried and cooled.

[0009] S3, XRF detection: A corresponding measurement method was established on the X-ray fluorescence spectrometer, the optimal measurement conditions for each component were selected, the existing interference factors were corrected, and the corresponding working curve was obtained by calculation and regression. The working curve was then used to test the content of silicon, calcium, aluminum, and phosphorus in the sample pieces.

[0010] The mass ratio of the sample, lithium carbonate and potassium nitrate is 1: (4-6): (0.5-1.5); The amount of anhydrous lithium tetraborate added is to fill the inner-lined crucible to 6 g.

[0011] In step S102, the pre-oxidation conditions are: keeping warm at 500±50°C for 20±5 minutes, heating from 500±50°C to 750±50°C for 15±5 minutes, and keeping warm at 750±50°C for 10±5 minutes.

[0012] The mass concentration of the lithium bromide is 25-35%, and the amount added is 5-7 drops.

[0013] In step S2, the automatic sample melting procedure is shown in Table 1.

[0014] Table 1 Automatic melting machine melting condition settings

[0015] The sample particle size is less than 0.097 mm; In step S2, the drying method is: drying in an oven at 105°C to 110°C for 1 h to 2 h; Cooling method: Cool to room temperature in a desiccator.

[0016] The principle of the present invention is to mix a sample with lithium carbonate and potassium nitrate, heat and pre-oxidize it in a prefabricated lithium tetraborate crucible, and then melt it with lithium tetraborate at high temperature to form a glass melt. The X-ray fluorescence intensity of the component to be tested is measured under pre-set measurement conditions of an X-ray fluorescence spectrometer. A working curve is created using a certified standard sample, with the intensity of the characteristic X-ray of the component to be tested in the standard sample as the ordinate and the standard value of the component to be tested in the standard sample as the abscissa. The sample's measurement results are calculated from the working curve based on the sample's X-ray fluorescence intensity.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention pre-treats the silicon nitride alloy and then melts it to make a glass sheet. The X-ray fluorescence spectrometer is used to quickly determine the content of multiple elements such as silicon, calcium, aluminum, and phosphorus in the alloy. For elements with higher content of silicon, it is not necessary to dilute the test solution and the measurement can be directly performed. This is a technological innovation and the measurement results are fast and accurate. Secondly, this method adopts a new sample pre-treatment procedure and method. By using a lithium tetraborate-lined crucible, adding a certain proportion of oxidant and flux, and setting a suitable sample pre-melting oxidation procedure, the rare earth nitrogen alloy can be made into a glass casting sheet sample that meets the measurement requirements of the X-ray fluorescence instrument, thereby realizing the simultaneous testing of the content of multiple components in the alloy by X-ray fluorescence spectrometry. This has achieved a great progress in silicon nitride alloy testing technology and improved the timeliness, precision and accuracy of the analysis.

[0018] The present invention provides a fused glass sheet method for rapidly determining multiple components of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys. This method not only greatly saves detection time and personnel energy, allowing more work to be done and improving detection efficiency, but also saves electricity and gas expenses, reduces detection costs, and fills the gap in the lack of a method for rapidly and accurately determining these elements in rare earth nitrogen alloys.

[0019] The X-ray fluorescence spectrometry method provided by the present invention for rapidly and simultaneously determining the major and minor multi-component amounts of silicon, calcium, aluminum, and phosphorus in a silicon nitride alloy has the advantages of high efficiency, safety, low cost, and rapidity. A relatively high silicon content can be directly determined without diluting the test solution, which not only greatly saves detection time and personnel energy, allowing more work to be done and improving detection efficiency, but also saves electricity and gas costs, reduces detection costs, and fills the gap in the lack of a method for rapidly and simultaneously determining these elements in rare earth nitrogen alloys. This is an important innovation in the method for rapidly and accurately determining the contents of multiple elements in rare earth nitrogen alloys, can fill the gap in domestic pretreatment of such samples, and has very strong application prospects and great social benefits. DETAILED DESCRIPTION

[0020] The present invention will be further described below with reference to the examples, but is not limited thereto.

[0021] 1. Instruments and reagents X-ray fluorescence spectrometer: ZSXPrimusIV; Melting machine: HNJC-T4; muffle furnace; Electronic balance (accuracy 0.0001g); Yellow platinum crucible (95% platinum + 5% gold, 30-70mL); Anhydrous lithium tetraborate (Li2B4O7, dry and anhydrous state); Anhydrous lithium carbonate (Li2CO3, dry and anhydrous state); Potassium nitrate, solid; Lithium bromide solution (30% LiBr): Weigh 30 g of analytical grade lithium bromide and dissolve it in 100 mL of pure water; Anhydrous lithium tetraborate lined crucible: made of anhydrous lithium tetraborate, open round bowl shape, bottom diameter 26 mm, top diameter 36 mm, height 12 mm, weighing about 5 g.

[0022] 2. Experimental methods S1. Pretreatment procedure for preparing the sample molten glass sheet: Weigh the mass of the anhydrous lithium tetraborate-lined crucible, denoted as m. Weigh (6-m) g of anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold molten sample crucible. Transfer 0.2000 g of sample, 1.0000 g of lithium carbonate, and 0.2000 g of potassium nitrate to a 50 mL glass beaker. Stir thoroughly with a glass rod, then transfer the mixture to a pre-weighed anhydrous lithium tetraborate pre-cast crucible. Place the pre-cast lithium tetraborate crucible in the platinum-gold crucible. Place the crucible in a muffle furnace heated to 500°C. Hold the temperature for 20 minutes, then raise the temperature to 750°C over 15 minutes. Hold the temperature for 10 minutes, remove the sample, and cool it before casting.

[0023] S2. Add 6 drops of lithium bromide to the pretreated crucible. Place the crucible in an automatic melting machine preheated to 1050°C. Follow the automatic melting program to form a glass melt. Dry in a 110°C oven for 1 hour, cool to room temperature, label, and place in a desiccator for testing. The automatic melting program is shown in Table 2.

[0024] Table 2 Automatic melting machine melting condition settings

[0025] S3. XRF testing: Prepare samples of standard samples, establish corresponding measurement methods on the X-ray fluorescence spectrometer, select the best measurement conditions for each component, correct the existing interference factors, calculate the regression to obtain the corresponding working curve, and then use the working curve to test the content of silicon, calcium, aluminum and phosphorus in the sample pieces respectively.

[0026] Embodiment 1: Accurately weigh the mass of the anhydrous lithium tetraborate-lined crucible, denoted as m. Weigh (6-m) g of anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold crucible. Transfer 0.2000 g of silicon nitride alloy #1, 1.0000 g of lithium carbonate, and 0.2000 g of potassium nitrate to a 50 mL glass beaker. Stir thoroughly with a glass rod and transfer the mixture to a pre-weighed anhydrous lithium tetraborate crucible. The pre-weighed lithium tetraborate crucible is then placed inside the platinum-gold crucible. The crucible is then placed in a muffle furnace heated to 500°C. After holding this temperature for 20 minutes, the temperature is raised to 750°C over 15 minutes and held for 10 minutes. Remove the crucible, cool it, and add 6 drops of lithium bromide to the pre-treated crucible. The crucible is then placed in an automatic fusion furnace preheated to 1050°C. A fused sheet is formed on the fusion program. After cooling, mark the temperature and place it in a desiccator for testing. The results are shown in Table 3.

[0027] Example 2: Accurately weigh the mass of the anhydrous lithium tetraborate-lined crucible (m). Weigh (6-m)g of anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold crucible. Transfer 0.2000g of silicon nitride alloy #2, 1.0000g of lithium carbonate, and 0.2000g of potassium nitrate to a 50mL glass beaker. Stir thoroughly with a glass rod and transfer the mixture to a pre-weighed anhydrous lithium tetraborate crucible. The pre-weighed lithium tetraborate crucible is then placed inside the platinum-gold crucible. The crucible is then placed in a muffle furnace heated to 500°C. After holding the temperature for 20 minutes, the temperature is raised to 750°C over 15 minutes and held for 10 minutes. Remove the crucible, cool it, and add 6 drops of lithium bromide to the pre-treated crucible. The crucible is then placed in an automatic fusion furnace preheated to 1050°C. A fused sheet is formed on the fusion program. After cooling, mark the temperature and place it in a desiccator for testing. The results are shown in Table 3.

[0028] Example 3: Accurately weigh the mass of the anhydrous lithium tetraborate-lined crucible (m). Weigh (6-m)g of anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold crucible. Transfer 0.2000g of silicon nitride alloy #3, 1.0000g of lithium carbonate, and 0.2000g of potassium nitrate to a 50mL glass beaker. Stir thoroughly with a glass rod and transfer the mixture to a pre-weighed anhydrous lithium tetraborate crucible. The pre-weighed lithium tetraborate crucible is then placed inside the platinum-gold crucible. Place the crucible in a muffle furnace heated to 500°C and hold for 20 minutes. Then, heat it to 750°C over 15 minutes and hold for 10 minutes. Remove the crucible, cool it, and add 6 drops of lithium bromide to the pre-treated crucible. Place the crucible in an automatic fusion furnace preheated to 1050°C. Melt the sample into a sintered sample using the fusion program. After cooling, mark the melt and place it in a desiccator for testing. The results are shown in Table 3.

[0029] Table 3 Test results

[0030] As can be seen from the table, the detection method of the present invention has high accuracy.

Claims

1. A method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry, characterized in that: The following steps are involved: S1. Preprocessing: S101. Weigh ingredients: Weigh the sample, lithium carbonate, and potassium nitrate, stir them evenly, and transfer them into a prefabricated crucible of anhydrous lithium tetraborate; weigh anhydrous lithium tetraborate and spread it evenly on the bottom of a platinum-gold crucible, and then place the prefabricated crucible of anhydrous lithium tetraborate into the platinum-gold crucible; S102, pre-oxidation: Place the platinum-gold crucible in a muffle furnace heated to 500±50°C, keep warm, then heat to 750±50°C, keep warm, take out, and cool; S2, melting: Lithium bromide is added dropwise to the platinum-gold crucible, and the crucible is placed in an automatic melting machine that has been preheated to the melting temperature, and the sample is automatically melted to form a glass frit, dried, and cooled; S3, XRF detection: A corresponding measurement method was established on the X-ray fluorescence spectrometer, the optimal measurement conditions for each component were selected, the existing interference factors were corrected, and the corresponding working curve was obtained by calculation and regression. The working curve was then used to test the content of silicon, calcium, aluminum, and phosphorus in the sample pieces.

2. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: The mass ratio of the sample, lithium carbonate and potassium nitrate is 1: (4-6): (0.5-1.5).

3. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: The amount of anhydrous lithium tetraborate added is to fill the inner-lined crucible to 6 g.

4. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: In step S102, the pre-oxidation conditions are: keeping warm at 500±50°C for 20±5 minutes, heating from 500±50°C to 750±50°C for 15±5 minutes; keeping warm at 750±50°C for 10±5 minutes.

5. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: The mass concentration of the lithium bromide is 25-35%, and the amount added is 5-7 drops.

6. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: In step S2, the automatic melting procedure is as follows: melting temperature 1050±50°C; static melting time 60±10s; swing melting time 1200±60s; crucible rotation speed 60±10rpm.

7. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: The sample particle size is less than 0.097 mm.

8. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: In step S2, the drying method is: drying in an oven at 105°C to 110°C for 1 hour to 2 hours.

9. The method for rapid and simultaneous determination of silicon, calcium, aluminum, and phosphorus in silicon nitride alloys by X-ray fluorescence spectrometry according to claim 1, characterized in that: In step S2, the cooling method is: cooling to room temperature in a desiccator.

Citation Information

Patent Citations

  • Manufacturing method of alloy molten sample wafer

    CN111060369A

  • Fusion casting glass sheet method for rapidly determining potassium, sodium, silicon, calcium, magnesium, aluminum, titanium, sulfur and phosphorus in coal ash

    CN119534512A